The Effectiveness Of Mini-Action Games In Reducing Hyperactivity And Attention Deficit Behaviors Among Primary School Students - Marwah Ali Hamzah (Musamus Journal of Physical Education and Sport (MJPES), 2026)
The purpose of this paper is to prepare miniature action games exercises to reduce hyperactivity and attention deficit behaviors among elementary school students. This study aimed to identify the impact of mini-action games on reducing hyperactivity and attention deficit behaviors among elementary school students. The experimental method, specifically a two-group equivalent group design, was used as it was deemed most suitable for the research problem. The research community consisted of 123 fourth-grade students at Al-Sudair Elementary School for Boys during the 2024-2025 academic year, divided into three sections (A, B, C, and D). A random sample of 31 students was selected from section C. These students were then randomly divided into two groups of 10 each: an experimental group and a control group. Ten students were selected for the pilot study, while one student was excluded due to absenteeism. This resulted in a sample size of 25.20% of the total research community. Mini-action games were developed after a comprehensive review of resources on mini -scale games and recreation to ensure the inclusion of appropriate exercises that could potentially reduce hyperactivity and attention deficit behaviors. To achieve this, the researcher identified the necessary needs for the exercises and determined the desired objectives of designing them. The most important conclusions reached were that the mini-action games helped reduce hyperactivity and attention deficit in elementary school students. The mini-action games prepared by the researcher were age-appropriate for elementary school students. Furthermore, there was a significant increase in students’ participation in the mini-action games prepared by the researcher during physical education classes compared to regular lessons.